Dietary supplementation of branched-chain amino acids increases muscle net amino acid fluxes through elevating their substrate availability and intramuscular catabolism in young pigs. Issue 7 (27th April 2017) - Zheng, Liufeng; Zuo, Fangrui; Zhao, Shengjun; He, Pingli; Wei, Hongkui; Xiang, Quanhang; Pang, Jiaman; Peng, Jian
Abstract: Branched-chain amino acids (BCAA) have been clearly demonstrated to have anabolic effects on muscle protein synthesis. However, little is known about their roles in the regulation of net AA fluxes across skeletal muscle in vivo . This study was aimed to investigate the effect and related mechanisms of dietary supplementation of BCAA on muscle net amino acid (AA) fluxes using the hindlimb flux model. In all fourteen 4-week-old barrows were fed reduced-protein diets with or without supplemental BCAA for 28 d. Pigs were implanted with carotid arterial, femoral arterial and venous catheters, and fed once hourly with intraarterial infusion of p -amino hippurate. Arterial and venous plasma and muscle samples were obtained for the measurement of AA, branched-chain α -keto acids (BCKA) and 3-methylhistidine (3-MH). Metabolomes of venous plasma were determined by HPLC-quadrupole time-of-flight-MS. BCAA-supplemented group showed elevated muscle net fluxes of total essential AA, non-essential AA and AA. As for individual AA, muscle net fluxes of each BCAA and their metabolites (alanine, glutamate and glutamine), along with those of histidine, methionine and several functional non-essential AA (glycine, proline and serine), were increased by BCAA supplementation. The elevated muscle net AA fluxes were associated with the increase in arterial and intramuscular concentrations of BCAA and venous metabolites including BCKA and free fatty acids, and were also related to the decrease in the intramuscular concentration of 3-MH. Correlation analysis indicated that muscle net AA fluxes are highly and positively correlated with arterial BCAA concentrations and muscle net BCKA production. In conclusion, supplementing BCAA to reduced-protein diet increases the arterial concentrations and intramuscular catabolism of BCAA, both of which would contribute to an increase of muscle net AA fluxes in young pigs.